The Queen : her life - Morton, Andrew, 1953- (Grand Central Publishing, 2022)
"Renowned biographer Andrew Morton takes an in-depth look at Britain's longest reigning monarch, exploring the influence Queen Elizabeth had on both Britain and the rest of the world for much of the last century. From leading a nation struggling to restore itself after the devastation of the Second World War to navigating the divisive political landscape of the present day, Queen Elizabeth was a reluctant but resolute queen. This is the story of a woman of unflagging self-discipline who will long be remembered as mother and grandmother to Great Britain, and one of the greatest sovereigns of the modern era"--